Scl is required for dorsal aorta as well as blood formation in zebrafish embryos. - Patterson, L; Gering, M; Patient, R (2005)
Blood and endothelial cells arise in close association in developing embryos, possibly from a shared precursor, the hemangioblast, or as hemogenic endothelium. The transcription factor, Scl/Tal1 (stem cell leukemia protein), is essential for hematopoiesis but thought to be required only for remodeling of endothelium in mouse embryos. By contrast, it has been implicated in hemangioblast formation in embryoid bodies. To resolve the role of scl in endothelial development, we knocked down its synthesis in zebrafish embryos where early precursors and later phenotypes can be more easily monitored. With respect to blood, the zebrafish morphants phenocopied the mouse knockout and positioned scl in the genetic hierarchy. Importantly, endothelial development was also clearly disrupted. Dorsal aorta formation was substantially compromised and gene expression in the posterior cardinal vein was abnormal. We conclude that scl is especially critical for the development of arteries where adult hematopoietic stem cells emerge, implicating scl in the formation of hemogenic endothelium.